A Speculative Poetics of Tammuz: Myth, Sentiment, and Modernism in Twentieth Century Arabic Poetry - Al-Rayes, Hamad (Labyrinth, 2020)
In this paper, I attempt to read the poetic principle behind the Tammuzi movement of modern Arabic poetry through the lens of speculative poetics. While speculative-poetic accounts of modern poetry, such as those provided by Allen Grossman, blazed new paths connecting poetry to personhood in modernity, their application to the development of modern poetry outside of Europe remains limited by their self-avowed focus on European history. This paper will outline a critical corrective to speculative poetics which, I argue, can be of value in extending its domain of application to Arabic projects of poetic modernity, particularly the two tendencies of "free verse" and "commitment" poetry that emerged out of the Tammuzi movement.